Competências do assistente social na Intervenção com utentes institucionalizados, vítimas de abandono: https://doi.org/10.53809/TS_ISS_2023_n.4_92-105 ("Temas Sociais" Journal, 2023)
According to the literature, the abandonment of disabled elderly people, who are the majority of the users of the Integrated Long-term Care Units (UCCI), has been increasing in Portugal. However, little is known about the work done by the social worker to improve the situation of these users and, above all, which skills are mobilized in their intervention. In response to this situation, the general objective of this study was to identify the competences of social workers in the intervention with institutionalized users in UCCI-ULDM and UMDR, victims of abandonment. The sample is composed of 18 professionals, randomly selected after division by NUTS II. The theoretical model used for the identification and assessment of competencies was the one by Le Boterf (2003). A mixed methodology was used, through the Delphi method, applying an open survey, in a first phase, and a questionnaire survey, with a 5 point Likert scale, in a second phase. A Focus Group was held with seven professionals who had, in the previous phases, answered the questionnaires. The results allowed identifying the most valued competencies by professionals in the resolution of dropout problems in the UCCI-ULDM and UMDR, related to know-how, and the most used strategies that result from teamwork/networking.